The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.scitotenv.2016.11.130
|View full text |Cite
|
Sign up to set email alerts
|

Bromine soil/sediment enrichment in tidal salt marshes as a potential indicator of climate changes driven by solar activity: New insights from W coast Portuguese estuaries

Abstract: This paper aims at providing insight about bromine (Br) cycle in four Portuguese estuaries: Minho, Lima (in the NW coast) and Sado, Mira (in the SW coast). The focus is on their tidal marsh environments, quite distinct with regard to key biophysicochemical attributes. Regardless of the primary bromide (Br) common natural source, i.e., seawater, the NW marshes present relatively higher surface soil/sediment Br concentrations than the ones from SW coast. This happens in close connection with organic matter (OM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 125 publications
1
2
0
Order By: Relevance
“…4A, C, D) throughout AD 1654-1725 (similar to the WP1 time frame), in which T. salsa/irregularis dominates (87-52%; mean 66%). This supports an increase in wetness in the studied area during the WP1 period, concomitant with higher contents of bromine and organic matter (OM) in the marsh's soils/sediments, both representative of rainy/colder conditions (Moreno et al 2015(Moreno et al , 2017b. Geochemical data from this marsh also revealed a maximum of terrestrial OM contribution at this time (de la Rosa et al 2012), moreover supporting increased continental runoff, and thus rainfall.…”
Section: Wine Production and Foraminiferal Time Series Variabilitysupporting
confidence: 67%
“…4A, C, D) throughout AD 1654-1725 (similar to the WP1 time frame), in which T. salsa/irregularis dominates (87-52%; mean 66%). This supports an increase in wetness in the studied area during the WP1 period, concomitant with higher contents of bromine and organic matter (OM) in the marsh's soils/sediments, both representative of rainy/colder conditions (Moreno et al 2015(Moreno et al , 2017b. Geochemical data from this marsh also revealed a maximum of terrestrial OM contribution at this time (de la Rosa et al 2012), moreover supporting increased continental runoff, and thus rainfall.…”
Section: Wine Production and Foraminiferal Time Series Variabilitysupporting
confidence: 67%
“…A comparison of several studies has shown that the wide variation of bromine contents in soils can be traced back to two main factors of influence. First, bromine concentration in soil mainly depends on the soil moisture content, and second, the bromine content of soil is positively correlated with the content of soil organic matter (Flury and Papritz 1993;Neal et al 2007;Moreno et al 2017). Since soil properties can influence related bioaccumulation and toxicity of bromine, it is important to determine soil parameters along with bromine concentrations in soils.…”
Section: Bromine Chemistry In Soil and Implications For Impact Characmentioning
confidence: 99%
“…In nature, Br is mainly concentrated in seawater in the form of ions, and the biggest natural reservoir is the ocean [44]. Br has historically been utilized in combination with Cl as a geochemical indicator for seawater intrusion in coastal regions and alone as a paleosalinity proxy and stratigraphic marker in cores [45].…”
Section: Discussionmentioning
confidence: 99%